Classical Macrophage Activation Up-Regulates Several Matrix Metalloproteinases through Mitogen Activated Protein Kinases and Nuclear Factor-κB - Huang, Wei-Chun (Public Library of Science, 2012)
Remodelling of the extracellular matrix (ECM) and cell surface by matrix metalloproteinases (MMPs) is an important function of monocytes and macrophages. Recent work has emphasised the diverse roles of classically and alternatively activated macrophages but the consequent regulation of MMPs and their inhibitors has not been studied comprehensively. Classical activation of macrophages derived in vitro from un-fractionated CD16(+/−) or negatively-selected CD16(−) macrophages up-regulated MMP-1, -3, -7, -10, -12, -14 and -25 and decreased TIMP-3 steady-state mRNA levels. Bacterial lipopolysaccharide, IL-1 and TNFα were more effective than interferonγ except for the effects on MMP-25, and TIMP-3. By contrast, alternative activation decreased MMP-2, -8 and -19 but increased MMP -11, -12, -25 and TIMP-3 steady-state mRNA levels. Up-regulation of MMPs during classical activation depended on mitogen activated protein kinases, phosphoinositide-3-kinase and inhibitor of κB kinase-2. Effects of interferonγ depended on janus kinase-2. Where investigated, similar effects were seen on protein concentrations and collagenase activity. Moreover, activity of MMP-1 and -10 co-localised with markers of classical activation in human atherosclerotic plaques in vivo. In conclusion, classical macrophage activation selectively up-regulates several MMPs in vitro and in vivo and down-regulates TIMP-3, whereas alternative activation up-regulates a distinct group of MMPs and TIMP-3. The signalling pathways defined here suggest targets for selective modulation of MMP activity.